Analysis Of Customer Relationship Management And Services Marketing In Petroleum Retail Outlets In India - Jeenath Laila N,; Mohamed Rizwan, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Owing to globalization, an excessive degree of competitiveness, along with an organization’s work culture, the Indian scenario has been altering radically. Petroleum is a commodity of "product with the same price". This field was conquered by the Indian Government for more than half a millennium, where marketing had no or else very lesser involvement. This study analyzes Customer Relationship Management (CRM) and services marketing in petroleum Retail Outlets (ROs) in India. By designing a set of questionnaires concerning the CRM and marketing strategies in petroleum, the presented study is conducted. The questionnaires were distributed to 700 participants of which only 657 respondents have been gathered from the survey; also, 43 respondents were rejected since the response is not clear. The questionnaires were prepared by utilizing a 5-point Likert scale. The quantile regression of price changes and the stock market, consumption of fuel, consumer preference and reliability in petroleum outlets, and consumer preference choice were analyzed and tested. The result exhibited that the customer relationship and marketing strategies enhanced the profit of the petroleum business and sustained the market.